1985
DOI: 10.1159/000249466
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Significance of Organ-Specific Autoimmune Disorders (Clinical, Latent or only Autoantibodies) in Patients with Vitiligo

Abstract: The frequency of autoimmune disorders was determined in 373 vitiligo patients and in controls matched for sex, age and race. Vitiligo patients had an increased frequency of clinical autoimmune diseases of thyroid (7.5%), stomach (0.8%), parathyroid (1%), adrenal gland (1.3%). Vitiligo patients, without clinical signs of overt autoimmune diseases, also had a statistically significant increase in the frequency of gastric parietal cell (p < 0.001), thyroid microsomal (p < 0.05) and adrenal autoantibodies (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
62
5
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 9 publications
9
62
5
5
Order By: Relevance
“…From our review of the literature, the presence of different circulating autoantibodies in vitiligo patients varied from 2 to 70% [7,9,10,20,21]; these data are also roughly in agreement with our observations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…From our review of the literature, the presence of different circulating autoantibodies in vitiligo patients varied from 2 to 70% [7,9,10,20,21]; these data are also roughly in agreement with our observations.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless the analysis of existing data is difficult, owing to the heterogeneity of examined samples of patients and the diversity of searched autoantibodies. From our review of the literature, the prevalence of reported autoimmune diseases, according to history and/or clinical and instrumental findings, ranged from 2.7 to 55% [2,6,7,8,9,10,11,12,13,14,15,16,17,18]. The rates of autoimmune comorbidities in vitiligo patients appear to differ based on the population under study, according to ethnic differences [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two studies have reported an increased prevalence of various autoantibodies in patients with vitiligo [12,13]. A recent article has reported the presence of thyromegaly, antithyroid antibodies and thyroid dysfunction in significant numbers of children and adolescents with vitiligo [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of patients studied with vitiligo and APS I, complement-fixing antibodies directed against melanin-producing cells were identified (27,28). This immunoreactivity was not demonstrated in patients with isolated vitiligo or vitiligo associated with other autoimmune disorders (28) and can be found in patients with APS I many years before the development of vitiligo (29).Sera from patients with APS I are known to contain high titer autoantibodies, which makes APS I a suitable disease model for the identification of autoantigens. We recently demonstrated the presence of immunoreactivity against melanocyte nuclei in both hair follicles and epidermis in APS I patients (30).…”
mentioning
confidence: 98%
“…The etiology is largely unknown, but autoimmune mechanisms are thought to be involved. It is associated with various autoimmune disorders (16) such as insulin-dependent diabetes mellitus (17), thyroid disease (18,19), and pernicious anemia (20,21) and is often a component in autoimmune polyendocrinopathies (4) including APS I (1,5). Autoantibodies against melanocytes have been reported in patients with vitiligo unrelated to APS I (22,23), but the major autoantigens in vitiligo are yet to be identified.…”
mentioning
confidence: 99%